2020
DOI: 10.1177/1369433220971744
|View full text |Cite
|
Sign up to set email alerts
|

Numerical assessment of effective width in steel-concrete composite box girder bridges

Abstract: The present paper aims to determine numerically in the Abaqus® software the parameters that have the greatest influence on the effective width of steel-concrete composite box girder bridges. In the technical standards and in the literature, there is no specific recommendation for calculating the effective width in steel-concrete composite box girder bridge. As an alternative, the existing recommendations for steel-concrete composite I-girders are adopted. Therefore, in the absence of standards recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In view of the most relevant research cited, it can be observed that studies on the shear lag effect have a very varied focus. For the purposes of this work, papers that present a method for calculating the effective width of steel-concrete composite girder bridges were selected: Gara et al (2011), Zhu et al (2015), Yuan et al (2016) and Nicoletti et al (2021b), in addition to the standard recommendations of AASHTO (2017) and EN 1994-2-2 (CEN, 2005b. In section 3, these methods were explained and, in section 4, they were compared and discussed.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In view of the most relevant research cited, it can be observed that studies on the shear lag effect have a very varied focus. For the purposes of this work, papers that present a method for calculating the effective width of steel-concrete composite girder bridges were selected: Gara et al (2011), Zhu et al (2015), Yuan et al (2016) and Nicoletti et al (2021b), in addition to the standard recommendations of AASHTO (2017) and EN 1994-2-2 (CEN, 2005b. In section 3, these methods were explained and, in section 4, they were compared and discussed.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Based on a large amount of theoretical data from the parametric analysis performed, Yuan et al proposed Equation (14) to calculate the effective width coefficient. Nicoletti et al (2021b) numerically determined in the Abaqus ® software, in a qualitative and quantitative way, the parameters that exert the greatest influence on the effective width of steel-concrete composite box girder bridges. For this purpose, 260 simply supported models were evaluated, in which the study variables were the configuration of the cross section, the height of the slab, the length of the span, the arrangement of elements in the cross section and the degree of steel-concrete interaction.…”
Section: Yuan Et Al (2016)mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the existing studies [1,[5][6][7][8][9][10][11][12][13][14][15][16] concerning the definition of the effective width are based on cantilever or simply supported beams. However, continuous beams or semi-continuous beams (i.e., beams with semirigid joints at their extremities) are regularly met in buildings; in these beams, regions subjected to sagging and hogging bending are identified.…”
Section: Introductionmentioning
confidence: 99%